Endocrine and metabolic alterations in response to systemic inflammation and sepsis: a review article - Syed Faizan Mehdi; Muhammad Hamza Qureshi; Salman Pervaiz; Karishma Kumari; Edwin Saji; Mahnoor Shah; Ahmad Abdullah; Kamran Zahoor; Hafiza Amna Qadeer; Disha Kumari Katari; Christine Metz; Lopa Mishra; et al. (Molecular Medicine)
Abstract Severe sepsis is cognate with life threatening multi-organ dysfunction. There is a disturbance in endocrine functions with alterations in several hormonal pathways. It has frequently been linked with dysfunction in the hypothalamic pituitary-adrenal axis (HPA). Increased cortisol or cortisolemia is evident throughout the acute phase, along with changes in the hypothalamic pituitary thyroid (HPT) axis, growth hormone-IGF-1 axis, insulin-glucose axis, leptin, catecholamines, renin angiotensin aldosterone axis, ghrelin, glucagon, hypothalamic pituitary gonadal (HGA) axis, and fibroblast growth factor-21. These changes and metabolic alterations constitute the overall response to infection in sepsis. Further research is essential to look into the hormonal changes that occur during sepsis, not only to understand their potential relevance in therapy but also because they may serve as prognostic indicators.